Evaluation of enzymatic Pectin extraction by a recombinant Polygalacturonase (pgi) from apples and pears pomace of argentinean production and characterization of the extracted pectin - Franchi, María L. (2014)
Fil: Franchi, María L. Universidad Nacional de Rio Negro. Escuela de Producción, Tecnología y Medio Ambiente; Argentina.